HIGHER EDUCATION GAMIFICATION: THE TRINITY OF PBL AS A TOOL FOR EDUCATIONAL PROCESS MODERNIZATION - Savitska Viktoriіa; Krychkivska, Oksana (Physical and Mathematical Education, 2022)
Formulation of the problem. The article is devoted to the problems of modernization of the educational process in higher education based on the use of game technologies and their elements. The relevance of the study is due to the identified opportunities for the trinity of PBL (Points, Badges, and Leaderboards) as a tool to increase learning motivation among students. Materials and methods. The methodological basis is generally theoretical and empirical research methods. A review of modern scientific literature, periodicals, and scientific and methodological sources on the problem of gamification of higher education, their analysis, structuring, interpretation, and construction of logical conclusions was fulfilled. Systematization of prospects for the development of gamification in higher education using SWOT analysis was carried out. Results. The article considers the content of the main scientific approaches to the definition of "gamification in higher education". Problems and possibilities of using the game component of PBL in the educational process of higher education institutions are analyzed. Innovative variants of the application of the most universal game components of PBL in the educational process of higher school in the study of any discipline are offered. The study allowed substantiating the feasibility of gamification in higher education based on the results of generalization of theoretical sources, analytical information, and SWOT analysis. Conclusions. Based on the literature analysis, options for using the PBL trinity as a tool for modernizing the educational process in higher education are proposed. The use of game techniques, taking into account the trinity of PBL in the educational process, can be one of the mechanisms to increase students’ motivation and interest in learning disciplines, improve their involvement in learning, and heighten the level of competencies they acquire. The obtained results can be applied in designing various educational courses in the study process where game technologies are used.